Analisis Relevansi Media Youtube Kids Untuk Menstimulasi Kemampuan Menyimak Anak Usia 5-6 Tahun - Sintia Ahmad, Dewi; Wirman, Asdi (incrementapedia, 2021)
This research aims to determine the relevance of youtube kids to stimulate the listening skills of children aged 5-6 years. The design of this research is the descriptive qualitative study. Data collection techniques using youtube video analysis, journals, and articles about stimulation of listening ability and research related to this study. The data analysis techniques using content analysis, inductive analysis and descriptive analytics. The result showed youtube kids can enhance the listening skills of children aged 5-6 years. Youtube kids contains indicators of listening skills include: the ability to listen and match images, listen and imitate, listen and follow instruction, listen and repeat.